The contribution of epididymosomes to the sperm small RNA profile. Issue 6 (June 2019) - Trigg, Natalie A; Eamens, Andrew L; Nixon, Brett
Abstract : It is now well established that mature spermatozoa harbour a rich and diverse profile of small non-protein-coding regulatory RNAs (sRNAs). There is also growing appreciation that this sRNA profile displays considerable plasticity, being altered in response to paternal exposure to a variety of environmental stressors. Coupled with evidence that upon delivery to the oocyte at the moment of fertilisation, sperm-borne sRNAs are able to influence both early embryonic development and the subsequent health of the offspring, there is now interest in both the timing and degree of change in the composition of the sRNA cargo of sperm. Models in which such epigenetic changes are linked to the spermatogenic cycle are seemingly incompatible with the lack of overt phenotypic changes in the spermatozoa of affected males. Rather, there is mounting consensus that such changes are imposed on sperm during their transit and storage within the epididymis, a protracted developmental window that takes place over several weeks. Notably, since spermatozoa are rendered transcriptionally and translationally silent during their development in the testes, it is most likely that the epididymis-documented alterations to the sperm sRNA profile are driven extrinsically, with a leading candidate being epididymosomes: small membrane enclosed extracellular vesicles that encapsulate a complex macromolecular cargo of proteins and RNAs, including the sRNAs. Here, we review the role of epididymosome–sperm communication in contributing to the establishment of the sperm sRNA profile during their epididymal transit.